UTSim: A framework and simulator for UAV air traffic integration, control, and communication. (10th September 2019) - Al-Mousa, Amjed; Sababha, Belal H; Al-Madi, Nailah; Barghouthi, Amro; Younisse, Remah
The interest in unmanned systems especially unmanned aerial vehicle is continuously increasing. Unmanned aerial vehicles started to become of great benefit in many different fields. It is anticipated that unmanned aerial vehicles will soon become a main component of the future urban air traffic. The integration of unmanned aerial vehicles within existing air traffic environments has started getting the attention of researchers. Integrating unmanned systems in the real-world urban air traffic requires the development of tools and simulators to enable researchers in their ongoing efforts. In this article, a simulator called UTSim is introduced. The proposed simulator is built using the Unity platform. UTSim is capable of simulating unmanned aerial vehicle physical specification, navigation, control, communication, sensing and avoidance in environments with static and moving objects. The simulator enables studying and exploring several unmanned aerial vehicle air traffic integration issues like sense and avoid, communication protocols, navigation algorithms, and much more. UTSim is designed and developed to be easily used. The user can specify the properties of the environment, the number and types of unmanned aerial vehicles in the environment, and specify the algorithm to be used for path planning and collision avoidance. The simulator outputs a log file with a lot of useful information such as the number of sent and received messages, the number of detected objects and collided unmanned aerial vehicles. Three scenarios have been implemented in this article to present the capabilities of UTSim and to illustrate how it can benefit researchers in the field of integrating unmanned aerial vehicles in urban air traffic.